Qualitative Analysis and Documentary Method In International Educational Research - Bohnsack, Ralf; Pfaff, Nicolle; Weller, Wivian (Verlag Barbara Budrich, 2010)
You need to work with qualitative methods, especially the Documentary Method? This is your book: The first systematic introduction related to the application of the Documentary Method on group discussions, interviews, films and pictures. Since the book is based on a German- Brazilian cooperation, it also provides an overview of the state of the art in Germany and Brazil with regards to Educational Science. From the contents: · Qualitative Methods in Educational Science · The Documentary Method and the Interpretation of Group Discussions · The Documentary Method and the Interpretation of Interviews · The Documentary Method and the Interpretation of Pictures and Videos